RvD2 mitigates TNFɑ-Induced mitochondrial reactive oxygen species through NRF2 signaling in placental trophoblasts - Hahka, Taija; Sekar, Deekshika; Sahoo, Prakash Kumar; Ravi, Aiswariya; Freel, Colman; Krishnamoorthy, Chandan; Ramamurthy, Sankar; Rapoza, Rebekah; Drakowski, Rebecca; Akbar, Anum; VanOrmer, Matt; Thoene, Melissa; et al. (Frontiers in Physiology, 2025)
IntroductionHypertensive disorders of pregnancy (HDP) are marked by elevated levels of TNFα, which increases reactive oxygen species (ROS) and disrupts metabolism of trophoblasts. Resolvin D2 (RvD2), an omega‐3 fatty acid-derived lipid mediator, is known to resolve inflammation, but its role in protecting trophoblasts by promoting antioxidant responses to alleviate ROS remains unclear. Nuclear translocation of nuclear factor erythroid 2‐related factor 2 (NRF2) controls cellular defense mechanisms against oxidative stress and helps with the maintenance of cellular redox homeostasis. Upon translocation to nucleus, NRF2 activates the antioxidant response element (ARE), inducing the expression of genes that can mitigate ROS. Hence, we hypothesized that RvD2 activates NRF2 and prevents TNFα‐induced mitochondrial dysfunction in trophoblasts.MethodsWe investigated RvD2’s potential protective mechanisms against TNFα‐induced oxidative stress in trophoblasts by pretreating JEG cells with 100 nM RvD2, followed by exposure to 50 or 100 ng/mL TNFα.ResultsWe also observed that placental TNFα levels were elevated, while NRF2 protein levels were reduced in human HDP placental tissues compared to normotensive placentas. We demonstrate that RvD2 alone enhances NRF2 nuclear translocation, increases glutathione levels and mitochondrial function, and reduces mitochondrial ROS. In contrast, TNFα alone decreases nuclear NRF2 levels, increases mitochondrial ROS and oxygen consumption rates, and impairs migration. Notably, pretreatment of RvD2 before TNFα exposure protects against mitochondrial ROS, increases NRF2 levels, and restores mitochondrial oxygen consumption rates in trophoblasts.DiscussionThese findings demonstrate that RvD2 functions as a positive regulator of endogenous antioxidant properties by enhancing NRF2 levels and mitigating mitochondrial ROS in placental trophoblasts.